Drug-related problems and clinical risk factors relationship in hepatic cirrhosis patients - Amelia Lorensia; Widyati .; Aziz Hubeis; Hary Bagijo (Indonesian Journal of Pharmacy, 2011)
Diffusion  processes  in  hepatic  cirrhosis  is  characterized  with  fibrosis  and structural changed. Patients with cirrhosis are at risk to get problems because of the  effects  of  the  drugs  used  have  drug-related  problems  (DRPs),  due  to changes  in  heart  function  that  affects  many  aspects of  drug  pharmacokinetics. Therefore,  treatment  of  patient  with  hepatic  cirrhosis  should  consider  the  drug and  dose  adjustment  so  that  subsequent  problems  could  be  avoided.  The research  method  was  prospective  and  descriptive,  with  a  purposive  sampling technique.  Patients’s  treatment  were  monitoring  and analyzed.  Significance  of 0000  means  that  p  (0000)  <0.05,  then  the  Pearson  correlation  test  results  are H1a, ie there was a relationship between the numberof DRPs events by the total number of clinical risk factors of DRPs in patientswith cirrhosis. Therefore from this relationship could be expected to know the possible risk of DRPs in patients. The  increasing  number  of  clinical  risk  factors  DRPs in  patients  with  cirrhosis, indicate  thatthe  patient  should  receive  a  more  stringent  monitoring  of  the provision of therapy because the risk of experiencing DRPs more.Key words: cirrhosis, drug related problems (DRPs), clinical risk factors of DRPs